Ministry of Tourism Decree No. 979 of the Year 2014 Issued on 19/11/2014 = وزارة السياحة قرار رقم 979 لسنة 2014 صادر بتاريخ 19/11/2014 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic